Objective Image Quality Analysis of Convolutional Neural Network Light Field Coding - Medda, Daniele; Song, Wei; Perra, Cristian (European Workshop on Visual Information Processing, 2019)
Light field digital images are novel image modalities for capturing a sampled representation of the plenoptic function. A large amount of data is typically associated to a single sample of a scene, and data compression tools are required in order to develop systems and applications for light field communications. This paper presents the study of the performance of a convolutional neural network autoencoder as a tool for digital light field image compression. Testing conditions and a framework for the experimental evaluation are proposed for this study. Different encoders and coding conditions are taken into consideration, obtained results are reported and critically discussed.